การพัฒนากรอบสมรรถนะสำหรับพยาบาลวิชาชีพหน่วยอุบัติเหตุ และฉุกเฉิน โรงพยาบาลลานนา จังหวัดเชียงใหม่ - พนมวรรณ บำรุงผล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The development of a competency framework is a process used to obtain competencies that demonstrate the knowledge, skills, and attributes of nurses. The purpose of this developmental study was to develop a competency framework for the registered nurses of an emergency unit in Lanna Hospital, Chiang Mai Province, by applying the competency framework development model of Marrelli, Tondora, and Hoge (2005). The samples were chosen by purposive sampling and consisted of six emergency nurses and three experts. The instrument used was an interview guideline validated by three experts. The development process included: 1) reviewing the relevant literature, 2) interviewing emergency nurses, 3) developing a draft of the competency framework, and 4) content validating the draft of the competency framework. The results of the study revealed that the competency framework of registered nurses in the emergency unit consisted of 34 behavioral indicators which could be divided into five dimensions: 1) screening, which consisted of four behavioral indicators, 2) non-urgent nursing, which consisted of two behavioral indicators, 3) urgent nursing, which consisted of 10 behavioral indicators, 4) emergency nursing, which consisted of eight behavioral indicators, and 5) mass emergency management, which consisted of 10 behavioral indicators. The results of this study may be useful for nursing managers who wish to develop tools to evaluate the competency of registered nurses in an emergency unit of Lanna Hospital, Chiang Mai Province.